2022
DOI: 10.14295/bjs.v1i4.34
|View full text |Cite
|
Sign up to set email alerts
|

Elaboração de cerveja artesanal do estilo caxiri beer com adição de camu-camu (Myrciaria dubia)

Abstract: Em 2020, o Brasil apresentou crescimento de 14,4% no número de cervejarias com relação ao ano de 2021.  Este segmento vem ganhando espaço com estudos científicos que buscam inovações de cervejas com aromas e sabores mais pronunciados. Baseado nisso o presente estudo tem como objetivo elaborar e avaliar uma cerveja artesanal do estilo Caxiri Beer com adição de polpa de camu-camu. Os frutos de camu-camu foram selecionados, despolpados, branqueados e congelados até o momento do uso. Os frutos, a fécula de mandioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…(beer with pineapple pulp), which is typical for alcoholic beverages containing fruits. The increase in moisture in pineapple beer was influenced by the excess water present in the fruit pulp, making it more challenging for the yeast to reduce the extract, and it somewhat compromises the quality of the final beer (Gonçalves et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(beer with pineapple pulp), which is typical for alcoholic beverages containing fruits. The increase in moisture in pineapple beer was influenced by the excess water present in the fruit pulp, making it more challenging for the yeast to reduce the extract, and it somewhat compromises the quality of the final beer (Gonçalves et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The average pH value was 4.17 (pineapple pulp) and 4.07 (beer with pineapple pulp), consistent with Pinto et al (2015), who found values of 4.24, 4.10, and 4.10 for the addition of 10%, 15%, and 20% pineapple juice, respectively. Gonçalves et al (2022) state that when fruit juice is added to beer, there is a decrease in pH, and a pH < 4.5 in beer reduces the risk of pathogenic microorganism proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the potential industrial use of caxiri would face significant challenges due to the traditional and artisanal nature of the manufacturing process (Schwan et al, 2017), which differs substantially from large-scale production practices. However, industrialization is not impossible but requires special considerations: process standardization, quality control, production technology, preservation of authenticity, and legal and regulatory issues (Gonçalves et al, 2022. In summary, since the traditional caxiri manufacturing process takes into account specific fermentation practices, local ingredients, and even community involvement (Chacón Mayorga et al, 2021), the degradation of caxiri during industrialization can be a real challenge. Therefore, the industrialization of caxiri should be approached with caution and respect for local culture and traditions, making it more viable to establish partnerships with indigenous communities for small-scale production.…”
Section: Caxirimentioning
confidence: 99%
“…Furthermore, it is known that products like tucupi and jambu are already widely used as condiments in local cuisine and have the potential for global consumption (Costa et al, 2017). Finally, the fermentation of other native fruits such as cupuaçu, buriti, taperebá, bacuri, camucamu, and wild bee honey can be used for the large-scale production of fruit wines, beers, and vinegars (Dias et al, 2003;Pelais et al, 2008;Costa et al, 2018;Gonçalves et al, 2022). These examples highlight the remarkable ability of indigenous communities in the Amazon to develop unique and highly valued food products.…”
Section: Fermented Products From the Amazon Region: Potential For The...mentioning
confidence: 99%
“…Na indústria alimentícia é comumente usado para bebidas mistas para aumentar o teor de vitamina C e sua polpa é utilizada em sucos, néctar, geleia, sorvete, bala, iogurte, barra de cereais e bebidas alcoólicas. 79,81,[93][94][95][96] Na indústria cosmética, tem sido usado em xampus e protetor solar. 79 Na indústria farmacêutica, para produzir comprimidos e cápsulas como fonte natural de vitamina C. [97][98][99] Atualmente a crescente demanda industrial do camu-camu supera a oferta, o que sugere aumentar áreas de cultivos, uso de tecnologia para evitar perda do fruto após a colheita 80 caracterizar todas as enzimas que participam da produção de vitamina C de pelo menos uma das vias metabólicas.…”
Section: Vitamina C Em Myrciaria Dubia (Kunth) Mcvaugh (Camu-camu)unclassified